What are the determinants of student performance on an undergraduate accounting degree?. Issue 9 (21st October 2021) - Brook, Simon; Roberts, Martin
ABSTRACT: The objective of this study is to identify the factors which have a significant impact on the performance of students on an undergraduate accounting degree course. Previous research in this area has taken place over many years and has considered a number of factors which might influence performance such as: prior academic achievement, gender, age and numeracy. The findings of these studies have been quite mixed, perhaps reflecting differences in the institutions being considered, the courses analysed and the research methods adopted. This study follows a cohort of students who commenced an undergraduate accounting degree course at a UK University through to their graduation. It unites and tests all the key findings of the other previous studies in this area to determine the key factors affecting student performance. The results can inform universities in terms of their policies on admissions, teaching and retention and also inform students in deciding whether to apply for or continue with an accounting course. The results will also be of interest to academics delivering accounting courses and those with an interest in accounting education.